Diagnostic utility of integrated analysis of exome and transcriptome: Successful diagnosis of Au‐Kline syndrome in a patient with submucous cleft palate, scaphocephaly, and intellectual disabilities - Mamiko Yamada; Yuichi Shiraishi; Tomoko Uehara; Hisato Suzuki; Toshiki Takenouchi; Chihiro Abe‐Hatano; Kenji Kurosawa; Kenjiro Kosaki (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background A weakness of exome analysis lies in inability to characterize aberrant splicing other than those involving consensus donor‐acceptor sequence. To overcome this limitation, we developed a novel analytic method SAVNet that combines transcriptome and exome analysis which enabled the successful detection of carriers of splicing variants in the disease‐causing genes of autosomal recessive disorders within a normal cohort. However, the clinical utility of the SAVNet analysis in delineating splicing defects in patients without a diagnosis has yet to be documented. Method We performed SAVNet analysis using the integrated analysis of exome and transcriptome analysis from the peripheral blood of the patient. The patient is an undiagnosed Japanese female patient with submucous cleft palate, scaphocephaly and intellectual disability with no words at 8 years of age. Dysmorphic features included a long face, a short palpebral fissure, thick lips with an open month, premaxillary hypoplasia, a depressed nasal bridge, and satyr ears. Result A SAVNet analysis showed that a heterozygous intronic variant located at the −10 position of exon 5 of the HNRNPK gene on chromosome 9 created a new splice acceptor sequence “ag” and led to the incorporation of 9 intronic nucleotides into the coding sequence. The mutant protein would have three extra amino acid residues, Leu‐Leu‐Gln, inserted within the critical KH domain. The patient was diagnosed as having recently delineated Au–Kline syndrome, which is characterized by cleft palate, craniosynostosis, and intellectual disability. Conclusion The successful molecular diagnosis of the presently reported patient illustrates the diagnostic utility of the SAVNet analysis as an innovative way of implementing an integrated exome‐transcriptome analysis in clinical settings.